Design and Development of Integration of Physical and Juridical Data Application in Complete Systematic Land Registration Activities - Abinowo Abinowo; Bambang Suyudi; Wahyuni Wahyuni (BHUMI: Jurnal Agraria dan Pertanahan, 2019)
Collection of physical data and juridical data should be carried out together and simultaneously to reduce the potential for errors in identifying land divisions. The incomparable amount between the physical task force and the juridical task force causes the achievement of the juridical task force to be slower compared tothat of the physical task force. The complete systematic land registration target is increasing year by year and the progress of information technology is a potential solution to overcome the problems of physical data and juridical data integration. This study aims to design applications to speed up physical and juridical data connections, test the feasibility of external factors and the quality of use of ISO-9126. The study method used in the application design integration of physical data and juridical data is the research and development method. It was conducted by testing the results of the user evaluation test questionnaire processing on the external factor of feasibility test ISO-9126 and quality in using ISO 9126 to 26 respondents. The results of this study show that the application design has several stages including (1) planning, (2) design, (3) application construction, and (4)application implementation. Integration of physical and juridical data can be done by uploading juridical data into the application. Then, when the physical task force is in the location of the land division and place a coordinate point in the middle of the land division oriented to satellite imagery, the midpoint of the landdivision is then combined with the measured land division. The feasibility test of the application design on the external factors ISO-9126 has a sufficient value, so that the application can continue to be developed. Meanwhile, the ISO-9126 quality in use test value is high.